Evaluation of COVID-19 vaccine implementation in a large safety net health system - Chen, Jennifer C.; Gutierrez, Griselda; Kamran, Rachel; Terry, Jill; Telliyan, Armenui; Zaks, Camilo; Carson, Savanna L.; Brown, Arleen; Kim, Karen (Frontiers in Health Services, 2023)
Objectives To evaluate rapid COVID-19 vaccine clinic implementation from January-April 2021 in the Los Angeles County Department of Health Services (LACDHS), the second-largest US safety net health system. During initial vaccine clinic implementation, LACDHS vaccinated 59,898 outpatients, 69% of whom were Latinx (exceeding the LA County Latinx population of 46%). LACDHS is a unique safety net setting to evaluate rapid vaccine implementation due to system size, geographic breadth, language/racial/ethnic diversity, limited health staffing resources, and socioeconomic complexity of patients. Methods Implementation factors were assessed through semi-structured interviews of staff from all twelve LACDHS vaccine clinics from August-November 2021 using the Consolidated Framework for Implementation Research (CFIR) and themes analyzed using rapid qualitative analysis. Results Of 40 potential participants, 25 health professionals completed an interview (27% clinical providers/medical directors, 23% pharmacist, 15% nursing staff, and 35% other). Qualitative analysis of participant interviews yielded ten narrative themes. Implementation facilitators included bidirectional communication between system leadership and clinics, multidisciplinary leadership and operations teams, expanded use of standing orders, teamwork culture, use of active and passive communication structures, and development of patient-centered engagement strategies. Barriers to implementation included vaccine scarcity, underestimation of resources needed for patient outreach, and numerous process challenges encountered. Conclusion Previous studies focused on robust advance planning as a facilitator and understaffing and high staff turnover as barriers to implementation in safety net health systems. This study found facilitators that can mitigate lack of advance planning and staffing challenges present during public health emergencies such as the COVID-19 pandemic. The ten identified themes may inform future implementations in safety net health systems.